Analisis Beban Kerja dan Kompensasi terhadap Kepuasan Kerja Pegawai Non ASN Kantor Kecamatan Ngamprah Kabupaten Bandung Barat - Karisma Dinda Sabitha; Aam Rachmat Mulyana (Journal of Management and Bussines (JOMB), 2024)
This study aims to determine the influence of workload and compensation on job satisfaction of Non ASN Employees at the Ngamprah District Office, West Bandung Regency. The research method used is a quantitative research method. The results of the study from the calculation of the coefficient of determination of Workload and Compensation on job satisfaction of non ASN employees at the Ngamprah District Office were 65.6%. Based on the t-test and F-test, it was found that there was an influence of workload on job satisfaction, there was an influence of compensation on employee job satisfaction. In the simultaneous test, workload and compensation had an effect on job satisfaction of non ASN employees at the Ngamprah District Office. Conclusion, Workload, compensation have an impact on job satisfaction. Keywords: Workload, Compensation, Job Satisfaction